Glutathione S-transferase and multidrug-resistant phenotype in transitional cell carcinoma of the bladder - (:unkn) unknown (Elsevier B.V., 1996)
Objective: To asses the role of expression of resistance phenotypes in treatment failure in patients with invasive transitional cell carcinoma of the urinary bladder, since P-glycoprotein and glutathione S-transferase pi (GST) expression are implicated in resistance to various chemotherapy agents in different tumors. Methods: Tumor samples from P-glycoprotein and GST-pi were analyzed by immunohistochemistry. Results: P-glycoprotein and GST-pi were found in 35.7 and 42.9% of the samples, respectively. In 21.4% of the samples there was simultaneous expression of both proteins. No significant impact on prediction of tumor behavior was evident on statistical analysis by any one of the protein expressions. Conclusion: Drug resistance in transitional cell carcinoma may be through different mechanisms. Although the small sample size of this study precludes firm conclusions, the assessment of P-glycoprotein or GST-pi expression appears to be of little value as a predictor of response to chemotherapy in this group of tumors.
Keywords: Bladder neoplasm; Drug resistance; Immunohistochemistry